Impact of Adapted Physical Activity and Therapeutic Patient Education on Functioning and Quality of Life in Patients With Postacute Strokes. (October 2014) - Taricco, Mariangela; Dallolio, Laura; Calugi, Simona; Rucci, Paola; Fugazzaro, Stefania; Stuart, Mary; Pillastrini, Paolo; Fantini, Maria Pia; ,
Objective . The aim of this study was to assess whether the combination of Adapted Physical Activity (APA) and Therapeutic Patient Education (TPE) improves function and quality of life in survivors of strokes. Methods . This nonrandomized controlled study enrolled patients with mild to moderate hemiparesis referred to 2 physical medicine and rehabilitation units in Emilia-Romagna, Italy, 3 to 18 months after a single unilateral mild to moderate stroke. The experimental group (n = 126) received 16 APA sessions and 3 sessions of TPE, and the control group (n = 103) received usual care; 86.9% completed treatment. The main outcome measure was a 4-month change in gait endurance (that corresponds to 2 months after intervention in the experimental group), and secondary outcomes included the Short Physical Performance Battery, Berg Balance Scale, Barthel Index, Geriatric Depression Scale, 12-item Short-Form Health Survey, and Caregiver Strain Index. Changes in scores at 4 months were compared between groups using analysis of variance and controlling for group imbalance by means of the propensity score. Results . Gait endurance, physical performance, balance, and the physical component of the quality of life score increased significantly at 4 months in the APA group and remained stable in the control group. The propensity-adjusted between-group change was significant for these scores at P < .01. Conclusions . Our results confirm that it is feasible and potentially effective to implement APA programs for elderly patients with complex clinical conditions as early as 3 months after a stroke and suggest that, when combined with TPE, the effects of a postrehabilitation APA program are relatively enduring.